2007
DOI: 10.1016/j.jacc.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

64-Slice Computed Tomography Coronary Angiography in Patients With High, Intermediate, or Low Pretest Probability of Significant Coronary Artery Disease

Abstract: Computed tomography coronary angiography is useful in symptomatic patients with a low or intermediate estimated pretest probability of having significant CAD, and a negative CT scan reliably rules out the presence of significant CAD. Computed tomography coronary angiography does not provide additional relevant diagnostic information in symptomatic patients with a high estimated pretest probability of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
1
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(170 citation statements)
references
References 10 publications
(5 reference statements)
5
150
1
14
Order By: Relevance
“…Nonetheless, diagnostic accuracy of CTCA has mainly been studied in patient populations with high prevalences of CAD (1-3,5,6,8,10), because ICA as the reference standard is only justifiable in populations with high risk for CAD. Only little data have been published on the topic (19), and our study is the first to use the recently suggested intention-to-diagnose strategy for evaluation (20), where nonevaluative segments in CTCA are rated as false-positive findings.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, diagnostic accuracy of CTCA has mainly been studied in patient populations with high prevalences of CAD (1-3,5,6,8,10), because ICA as the reference standard is only justifiable in populations with high risk for CAD. Only little data have been published on the topic (19), and our study is the first to use the recently suggested intention-to-diagnose strategy for evaluation (20), where nonevaluative segments in CTCA are rated as false-positive findings.…”
Section: Discussionmentioning
confidence: 97%
“…The main field of employment for cardiac MDCT is coronary angiography of patients with low or medium pre-test probability of coronary artery disease [34]. Hence, the number of patients with poor cardiac function should be significantly small.…”
Section: Automatic Vs Semi-automatic Global Cardiac Function Assessmentmentioning
confidence: 99%
“…According to Bayes' theorem, patients with an intermediate pretest probability for a disease or condition are likely to benefit the most from diagnostic investigations (3). The use of cardiac CT and CT coronary angiography (CTA) for the exclusion of obstructive CAD (greater than 50% diameter stenosis) is therefore best applied in symptomatic patients with an intermediate pretest probability for CAD.…”
Section: Symptomatic Patientsmentioning
confidence: 99%